Cataloguing backlogs in academic libraries:a case study of some selected universities in Nigeria. (2010)
This study investigated the extent of cataloguing backlogs in academic libraries as well as the causes and remedies towards having a lasting solution to backlogs in academic libraries. A survey research design was employed for this study. The study population includes fifty cataloguers selected from ten academic libraries in Nigerian universities. A Cataloguing Backlog Assessment Questionnaire (CBAQ) was developed to elicit information from respondents and chi square statistical method was used in analyzing the data at 0.05 significance level. The result showed that there was no statistical significance in the size of backlog and volumes of acquisitions, level of automation as well as staff capacity. Based on these outcomes, recommendations were made that more librarians be involved in cataloguing processes and cataloguers with weak subject background be made to specialize in areas in which he or she is very strong, Universities increase budgetary allocations to libraries to enhance library automation and that para-professionals be trained to get involved in the cataloguing process.